Determinan Kebijakan Dividen pada Perusahaan Sektor Energi - M. Reza Oktananda; Puspa Rini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of financial variables—namely firm size, profitability, and capital structure (debt to equity ratio)—on dividend policy in energy sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. The method used is multiple linear regression with secondary data obtained from financial statements and annual reports, selected through purposive sampling, comprising 13 companies and 65 observations. The analysis results indicate that firm size has a significant positive effect on dividend policy, while profitability (ROA) and capital structure (debt to equity ratio) have significant negative effects. These findings confirm that larger firms tend to pay higher dividends, whereas high profitability and leverage exert downward pressure on dividend policy. This study contributes to the development of financial literature concerning the determinants of dividend policy in the energy sector.